Handbook of Practical Immunohistochemistry Frequently Asked Questions - Lin, Fan; Prichard, Jeffrey (Springer New York : Imprint: Springer, 2015)
In a conceptually current, quick-reference, Question & Answer format, the second edition of Handbook of Practical Immunohistochemistry: Frequently Asked Questions continues to provide a comprehensive and yet concise state-of-the-art overview of the major issues specific to the field of immunohistochemistry. With links to the authors Immunohistochemical Laboratory website, this volume creates a current and up-to-date information system on immunohistochemistry. This includes access to tissue microarrays (TMA) of over 10,000 tumors and normal tissue to validate common diagnostic panels and provide the best reproducible data for diagnostic purposes.   Fully revised and updated from the first edition, the new features of the second edition include over 200 additional questions or revised questions with an IHC panel to answer each question; over 250 new color photos and illustrations; over 20 new useful biomarkers; hundreds of new references; several new chapters to cover phosphoproteins, rabbit monoclonal antibodies, multiplex IHC stains, overview of predictive biomarkers, and integration of IHC into molecular pathology; many new coauthors who are international experts in a related field; many updated IHC panels using Geisinger IHC data collected from over 10,000 tumors and normal tissues; and updated appendices containing detailed antibody information for both manual and automated staining procedures.   Comprehensive yet practical and concise, the Handbook of Practical Immunohistochemistry: Frequently Asked Questions, Second Edition will be of great value for surgical pathologists, pathology residents and fellows, cytopathologists, and cytotechnologists.